Cohesive Parallel sentences in the Ashur Al-Naji story - sakineh mohammadi; Abbas Talebzade; seyed hosein seyedi (دراسات في اللغة العربيّة وآدابها)
Cohesion is marked as the prime criterion of seven-fold standard criteria that proves text comprehensively. Cohesion causes textual continuity via some tools and parallelism in which the parallelism factor entails basics (i.e., musically and grammatically) and interpretations (i.e., grammatically). The current article aims to focus on this factor with specific emphasis on these two arrangements. To follow the aim, we discussed the issues in Ashoor Al-Naji story. Following descriptive-analytical method, we underlined the prominent effect of society on the author's writing style; hence we also employed social critique analysis. The significance of the study was the notable influence of parallelism in the story, while the factor has been left unattended. In fact, the author applied parallelism at various levels in order to create regular rhythm or syntax. Indeed, textual components remain in readers' memory in virtue of parallelism factor. As a result, the author connected the textual components with each other and enhanced the impacts on readers' mind. In conclusion, this article discussed the parallelism role in this story accompanied basics and interpretations arrangements. Although we cannot ignore the importance of the basics in the story, the interpretations demonstrated more pronounced influences. The implication is that the author employed interpretations technique to organize syntactic interpretations and to achieve cohesion.